Novel nanocomposite synthesis of carboxymethyl cellulose coated to zero-valent iron supported on chitosan for simultaneous removal of heavy metals and pesticides in water: Performance and mechanism - Ahmad Abo Markeb; Javier Moral-Vico; Antoni Sánchez; Xavier Font (Results in Chemistry)
This study reports the synthesis and performance of a novel nanocomposite, CS@nZVI-CMC NC, consisting of zero-valent iron nanoparticles cross-linked to chitosan and coated to carboxymethyl cellulose. Also, the novelty of this work has been proven by eliminating several heavy metals and pesticides from aqueous solutions and drinking water simultaneously. The NC structure, morphology, size, and functional groups were investigated using advanced techniques such as TEM, SEM, XRD, FTIR, and BET. It showed that the surface area of the NC is found to be 127.95 m2/g and a pore volume of 0.659 cm3/g. A spherical shape of the nanoparticles with an average size of 8 ± 2 nm was obtained. The functional groups of the NC such as the NH, OH, CO, and CN were demonstrated using the FTIR analysis. The NC shows 96.91 %, 90.00 %, 60.61 %, 52.73 %, and 40.43 % simultaneous removal of Cr(VI), As(V), Cd(II), Pb(II) and Mn(II), respectively. Also, it demonstrates a significant simultaneous elimination of organochlorine pesticides: DDE, heptachlor, endrin aldehyde, endosulfan, and heptachlor epoxide, being 98.52 %, 94.01 %, 70.98 %, 65.39 %, and 63.02 % the elimination percentage, respectively. In addition, the NC exhibited the highest removal (77.09 %) of parathion methyl when simultaneously removing several organophosphorus pesticides. Adsorption mechanisms for the targeted pollutants were also studied, and adsorption and electron transfer were the predominant mechanisms. Therefore, this novel NC could be a promising water and wastewater treatment adsorbent.